The chemical structure, pharmacological activity, and clinical progress of Gentianae Radix et Rhizoma - Liu, Hongfang; Liu, Xiao; Liu, Sheng; Zhao, Feng (Frontiers in Pharmacology, 2025)
As pivotal medicinal resources in the Gentiana genus (Gentianaceae), Gentianae Radix et Rhizoma exhibit remarkable chemical diversity and multi-target pharmacological activities. This review highlights G. scabra Bunge., Gentiana rhodantha Franch., Gentiana manshurica Kitag., Gentiana veitchiorum Hemsl., and other species, compiling 172 constituents from literature (2004–2024) and traditional sources: terpenoids (66 iridoids, 47 triterpenoids, and others), flavonoids, lignans, and alkaloids. Iridoids (e.g., gentiopicroside, swertiamarin) and triterpenoids are key bioactive agents. Pharmaco-logically, Gentiana extracts target NF-κB and MAPK pathways to suppress in-flammation and oxidative liver injury via Nrf2 activation, while inducing tumor cell apoptosis (Bax/Bcl-2) and S/G2-M phase arrest to inhibit lung/liver cancer proliferation. They enhance gastrointestinal repair, regulate motility, and mitigate chronic pain through central-peripheral analgesic synergy. Clinically, gentiopicroside demonstrates hepatoprotective, antiviral, and neuroprotective effects, with applications in herpes zoster, non-alcoholic fatty liver disease, and metabolic disorders. This review represents the first comprehensive integration of multidimensional chemi-cal-pharmacological-clinical data on Gentianae Radix et Rhizoma constituents, aiming to promote the expanded application of Gentianae Radix et Rhizoma in the pharma-ceutical field, provide a scientific basis for further development and utilization, and lay a foundation for subsequent research and industrial development.